Gingival enlargements: A review - Anuja Namala; Dyamavva Halerolli; Preethi A Poonja; Prasanna Kumar Rao; Raghavendra Kini (Journal of Dental Problems and Solutions - Peertechz Publications, 2021)
Alteration in size of gingiva is one of the clinical features of periodontal disease. Increase in size of gingiva, which is termed as gingival enlargement or gingival over growth is a common clinical sign of gingival disease and a matter of great clinical concern. Increase in size alters the physiologic contour of gingiva, creates areas of plaque accumulation, intereferes with regular oral hygiene procedures and creates aesthetic problems. In severe cases, it interefere with mastication and phonation. Enlargement may involve one or more components of gingiva. Depending on the involvement of components of gingiva and distribution, gingival enlargement can be Localized, genaralized, marginal, papillary, diffuse and discrete. Depending on etiology and pathogenesis, it can be classified as inflammatory enlargement, fibrotic enlargement, combined enlargement, enlargement associated with systemic conditions, neoplastic enlargement and false enlargements.